2021
DOI: 10.3389/fneur.2021.720201
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Variants in ABHD16A Cause a Novel Psychomotor Developmental Disorder With Spastic Paraplegia

Abstract: Introduction: Hereditary spastic paraplegia is a clinically and genetically heterogeneous neurological entity that includes more than 80 disorders which share lower limb spasticity as a common feature. Abnormalities in multiple cellular processes are implicated in their pathogenesis, including lipid metabolism; but still 40% of the patients are undiagnosed. Our goal was to identify the disease-causing variants in Sudanese families excluded for known genetic causes and describe a novel clinico-genetic entity.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, extending the analysis to all genes covered by the exome, we identified variants in novel candidate genes in seven out of the ten remaining families (see Tables 1, 2), potentially raising our diagnostic success rate ceiling to 92% instead of 73%. One of those seven novel causative genes has been reported [30] and the others are under validation and will be reported elsewhere (unpublished data). According to the results of our two studies, most of the major autosomal recessive SCDs genes are present in Sudan (SACS, SPG11, FXN) and some of the major dominant ones as well (e.g., SCA3), but there is no single major gene causing SCDs in Sudan.…”
Section: Diagnosis Yieldmentioning
confidence: 93%
“…Furthermore, extending the analysis to all genes covered by the exome, we identified variants in novel candidate genes in seven out of the ten remaining families (see Tables 1, 2), potentially raising our diagnostic success rate ceiling to 92% instead of 73%. One of those seven novel causative genes has been reported [30] and the others are under validation and will be reported elsewhere (unpublished data). According to the results of our two studies, most of the major autosomal recessive SCDs genes are present in Sudan (SACS, SPG11, FXN) and some of the major dominant ones as well (e.g., SCA3), but there is no single major gene causing SCDs in Sudan.…”
Section: Diagnosis Yieldmentioning
confidence: 93%
“…181−183 Human subjects harboring deleterious mutations to ABHD16A suffer from developmental delays, intellectual disabilities, progressive spasticity of their limbs, and have anatomical anomalies in the brain. 181−183 In conjunction with studies from mice models, 92,95 lipidomics measurements on fibroblasts derived from HSP subjects with ABHD16A mutations 181,183 have shown that dysregulated PS-lyso-PS metabolism seems to be the likely causative factor for the pathology associated with this complicated form of HSP.…”
Section: Neurological Diseasesmentioning
confidence: 99%
“…Given this heightened expression of ABHD16A in the cerebellum, not surprisingly, very recent population level genomic and phenotypic mapping studies have shown that human subjects with deleterious genetic mutations to the ABHD16a gene suffer from diverse neurological developmental defects that are linked to complex hereditary spastic paraplegia (HSP) (discussed in section ). …”
Section: Enzymes Metabolizing Lyso-pss In Mammalian Cells and Tissuesmentioning
confidence: 99%
“…ABHD12 is mainly expressed in macrophages and microglia and throughout the brain. , ABHD16A is highly expressed in the brain, testis, muscle, and heart. , It has also been identified in human platelet and mouse megakaryocyte membranes and extracellular vesicles derived from colorectal cancer cells. , Both enzymes exist in the endoplasmic reticulum membrane and regulate the levels of signaling lipids in a concerted way. ABHD16A converts PS to lyso-PS, whereas ABHD12 hydrolyzes lyso-PS to glycerophosphoserine . Lyso-PS has several functions related to the immune response. Genetic deletion of ABHD12 leads to accumulation of lyso-PS in mice brain, leading to the neurodegenerative syndrome resembling the human neurological disorder PHARC (polyneuropathy, hearing loss, ataxia, retinitis pigmentosa, and cataract). , ABHD16A polymorphism is associated with Kawasaki disease, and total loss of function of ABHD16A has been detected in patients with complicated hereditary spastic paraplegia . Increased expression of ABHD16A has also been linked to the promotion of gastric cancer metastasis …”
mentioning
confidence: 99%
“…8,16 ABHD16A polymorphism is associated with Kawasaki disease, 17 and total loss of function of ABHD16A has been detected in patients with complicated hereditary spastic paraplegia. 18 Increased expression of ABHD16A has also been linked to the promotion of gastric cancer metastasis. 19 ABHD12 and ABHD16A possess a catalytic triad of Ser-His-Asp which functions through a well-established canonical esterase mechanism.…”
mentioning
confidence: 99%